Agro-Economic Performance of Jackfruit-Pineapple Agroforestry System in Madhupur Tract - Hasan, MK; Ahmed, MM; Miah, MG (Journal of Agriculture & Rural Development, 2008)
A survey was carried out in two villages of Durgapur union under Kapasia upazila of Gazipur district during January to March, 2005 to investigate profitability, problems and management system of practicing jackfruit-pineapple agroforestry practice. Result revealed that the existing jackfruit-pineapple agroforesty system is profitable and has a great contribution to the meet up of nutritional demand. There is a scope of adopting improved management practices and it may increase the total production. Among the various problems, jackfruit trunk borer is the major. Measures against insects, bat, hedgehog, squirrel etc., use of popular cultivar and training on improved management practices for development of jackfruit-pineapple agroforestry system were suggested to overcome these problems. Key words: Agro-economic performance, jackfruit-pineapple agroforestry system. DOI: http://dx.doi.org/10.3329/jard.v6i1.1672 J Agric Rural Dev 6(1&2), 147-156, June 2008